Vers une qualité sonore des espaces publics - Élise Geisler (Projets de Paysage)
The sound environment in urban areas is today saturated. Facing the noise, regulation and physical protection have been the first solutions implemented by public authorities. However, it is essential to propose more qualitative solutions in order to meet with the increasing social demand of wellbeing in urban areas. Only few sustainable sound improvements in urban public spaces have been identified despite punctual interventions of artists. Sound environment is complex, experiences and references are lacking while the research has been trying for the last thirties years to develop tools and methods. Couldn’t we meet the knowledge of the research on perception and sound environment with the theories and concepts of landscape in order to overcome this current landscaping dead end on sound areas ? Could the sensitive approach of landscapers bring new opportunities of intervention on sound environment by opening the way to others senses rather than only focusing on perception ?